Lecturer, Department of Applied Linguistics, Government College University, Faisalabad, Pakistan - Yadav, Amit; Sharma, Vijaylaxmi (International Journal of Psychosocial Rehabilitation, 2020)
This article aims to examine the role of law in social change and social transition and how law affects society and vice versa. Apart from this article also attempt to weigh the law’s effectiveness on the basis of society’s acceptance.